Pluto's Atmosphere from the 2015 June 29 Ground-based Stellar Occultation at the Time of the New Horizons Flyby - Sicardy, B. (2016)
We present results from a multi-chord Pluto stellar occultation observed on 2015 June 29 from New Zealand and Australia. This occurred only two weeks before the NASA New Horizons flyby of the Pluto system and serves as a useful comparison between ground-based and space results. We find that Pluto's atmosphere is still expanding, with a significant pressure increase of 5 +/- 2% since 2013 and a factor of almost three since 1988. This trend rules out, as of today, an atmospheric collapse associated with Pluto's recession from the Sun. A central flash, a rare occurrence, was observed from several sites in New Zealand. The flash shape and amplitude are compatible with a spherical and transparent atmospheric layer of roughly 3 km in thickness whose base lies at about 4 km above Pluto's surface, and where an average thermal gradient of about 5 K km(-1) prevails. We discuss the possibility that small departures between the observed and modeled flash are caused by local topographic features (mountains) along Pluto's limb that block the stellar light. Finally, using two possible temperature profiles, and extrapolating our pressure profile from our deepest accessible level down to the surface, we obtain a possible range of 11.9-13.7 mu bar for the surface pressure.